Human impact erodes chimpanzee behavioral diversity - Kühl, Hjalmar S; Boesch, Christophe; Kulik, Lars; Haas, Fabien; Arandjelovic, Mimi; Dieguez, Paula; Bocksberger, Gaëlle; McElreath, Mary Brooke; Agbor, Anthony; Angedakin, Samuel; Ayimisin, Emmanuel Ayuk; Bailey, Emma; et al. (My University, 2019)
Chimpanzees possess a large number of behavioral and cultural traits among nonhuman species. The “disturbance hypothesis” predicts that human impact depletes resources and disrupts social learning processes necessary for behavioral and cultural transmission. We used a dataset of 144 chimpanzee communities, with information on 31 behaviors, to show that chimpanzees inhabiting areas with high human impact have a mean probability of occurrence reduced by 88%, across all behaviors, compared to low-impact areas. This behavioral diversity loss was evident irrespective of the grouping or categorization of behaviors. Therefore, human impact may not only be associated with the loss of populations and genetic diversity, but also affects how animals behave. Our results support the view that “culturally significant units” should be integrated into wildlife conservation.